Rehtoreiden kokemuksia tärkeimmistä työtehtävistään ja liikuntaoppiaineen asemasta yläkoulussa - Peura, Aatos (2024)
The study aimed to examine the management of a Finnish primary school, the principals' experiences of their most important tasks as school leaders, and whether the principals' most essential tasks correspond to their work reality. In addition, the study investigated principals' experiences regarding the value and status of the physical education subject in primary school. The study also looked at the principal's influence on the appreciation of the physical education subject and the school's physical activity culture. The research was qualitative. Four principals of Finnish primary schools who had held the position of principal for more than ten years were interviewed. The research material was collected with a semi-structured thematic interview. Theory-guided content analysis was used as the analysis method. The results of the study confirmed the prior knowledge of principals' work reality; administrative tasks fill the principals' working days. The work is hectic, and the working days are filled with small, difficult-to-define tasks. The principals who participated in the study hoped for clarification of the principal's job description and more time for personnel management and the implementation of the school's development task. According to the principals' experience, they did not have enough time for the tasks and had to do them superficially. Based on the research, the position of physical education in primary school is good. The principals said the position has improved over the years and predicted it will improve in the coming years. In addition, the research results confirm previous knowledge about the principal's important influence on subject appreciation and the emergence of a physical activity culture within the school community.